The Impact of The Independence of The Central Bank of Libya on Inflation Rates In Libya For The Period (2012-2021) - El-Kailany عادل عبدالله; Delab أبوبكر خليفة دلعاب (Journal of Pure & Applied Sciences, 2022)
Given the importance of the Central Bank through its important position in establishing economic and monetary stability, the issue of the independence of the Central Bank has received great importance in economic and financial studies, due to its impact on economic activity and macroeconomic variables such as inflation, exchange rate and interest rate. Therefore, this study aims to know the impact of the independence of the Central Bank of Libya on inflation rates in Libya. To achieve the objectives of the study, the relationship between the independence of the Central Bank of Libya and one of the macroeconomic variables, which is inflation, was studied during the period from (2012-2021). . In order to obtain results that achieve the objectives of the study, the researcher used the Eviews10 software to analyses the data. The study revealed an inverse relationship between the independence of the Central Bank of Libya and inflation rates in the economy. An increase in the independence rate of the Central Bank by one unit will produce a decrease in inflation rates by 66.4% of units, and this result is in line with what was stated in the economic theory.